Transitional Complexity of Social Insect Immunity - Otani, Saria; Bos, Nick; Yek, Sze H. (Frontiers in Ecology and Evolution, 2016)
Genomic analyses between insects are often conducted by comparing host genomes to that of Drosophila. For honey bees, this led to the claim that the evolutionary transition to eusociality resulted in a reduction of immunity-related genes. Although this claim pervades the literature, contradictory evidence exists. Many genomic studies, however, are not comparable due to methodological differences, and only focus on the physiological aspect of the immune system, thus potentially missing other immunity components. We advocate more comprehensive comparative studies, as well as the analysis of insect-associated defensive microbiotas to improve our understanding of the complexity of social insect immunity.